Statelessness of Indonesian Citizens: Legal Analysis and Policy Critique of the S.A.K. Case - Nur Della, Rissa Ajeng; Rosyidah, Faizatur; Izzah, Ni’matul; Lestari, Anggun Tri; Bahiroh, Ibrizul (Jurnal Ilmu Pendidikan dan Humaniora, 2026)
The issue of Satria Arta Kumbara (S.A.K.) losing his citizenship after joining a foreign military highlights the tension between state sovereignty and human rights responsibilities. This study aims to analyze S.A.K.'s legal status based on Law Number 12 of 2006 (Law No. 12/2006), identify the implications of statelessness, and critique the government's policy response. The methods used are Normative Law (analysis of Articles 23f and 32 of Law No. 12/2006) enriched with a Qualitative-Contextual approach through interviews to examine policy criticism and humanitarian dimensions. The results of the study show that the status of Indonesian citizens S.A.K. normatively fulfills the elements for automatic loss (ex-lege) as an affirmation of the principle of single loyalty. However, in practice, S.A.K.'s status is uncertain because the government has not issued an official decision (Dhanis, personal communication via WhatsApp, December 6, 2025), which indicates a discrepancy between practice and regulations. This ambiguity has the potential to create a condition of statelessness that strips S.A.K. of his civil rights and diplomatic protection, a condition that contradicts the spirit of the Universal Declaration of Human Rights. The main criticism arises from the sharp procedural asymmetry: the sanction of losing status is instantaneous, while the path to recovery (reacquisition under Article 32) is long and bureaucratic, disproportionately prolonging the duration of statelessness. The conclusion of this study emphasizes the need for policy reform to be more adaptive and proportional. Three pillars of improvement are recommended: strengthening preventive policies, simplifying reacquisition procedures to minimize statelessness, and developing diplomatic humanitarian protocols